Comparative Expression Profiling of Snf2 Family Genes During Reproductive Development and Stress Responses in Rice - Guo, Mingliang; Zhao, Heming; He, Zhimei; Zhang, Wenchao; She, Zeyuan; Mohammadi, Mohammad Aqa; Shi, Chao; Yan, Maokai; Tian, Dagang; Qin, Yuan (Frontiers in Plant Science, 2022)
Sucrose non-fermenting 2 (Snf2) protein family, as chromatin remodeling factors, is an enormous and the most diverse protein family, which contributes to biological processes of replication, transcription, and DNA repair using the energy of adenosine triphosphate (ATP) hydrolysis. The members of Snf2 family proteins have been well characterized in Arabidopsis, rice, and tomato. Although this family received significant attention, few genes were identified uniquely for their roles in mediating reproductive development and stress tolerance in rice. In the present study, we comprehensively analyzed the expression profiling of Snf2 genes during reproductive development and biotic/abiotic stresses. Our results showed that five proteins (OsCHR712/715/720/726/739) were mainly localized in the nucleus, while OsCHR715/739 were also slightly expressed in the cell membrane. There were abundant cis-acting elements in the putative promoter of Snf2 genes, including dehydration, MeJA, MYB binding site for drought, ABA-responsive, and stress-responsive element. Most of the genes were induced immediately after Magnaporthe oryzae infection at 12 h post-infection (hpi). About 55% of the total genes were upregulated under salt and drought stresses during the entire time, and 22–35% of the total genes were upregulated at 3 h. It was noteworthy that the seven genes (OsCHR705, OsCHR706, OsCHR710, OsCHR714, OsCHR721, OsCHR726, and OsCHR737) were upregulated, and one gene (OsCHR712) was downregulated under salt and drought stresses, respectively. The deficiency of OsCHR726 mutations displayed a hypersensitive phenotype under salt stress. These results will be significantly useful features for the validation of the rice Snf2 genes and facilitate understanding of the genetic engineering of crops with improved biotic and abiotic stresses.